IMPLEMENTATION OF THE PBL MODEL INTEGRATED WITH STEM-EDP TO IMPROVE NUMERACY LITERACY SKILLS IN HIGH SCHOOL STUDENTS - Nasution, Tiara Anraladila; Abdurrahman, Abdurrahman; Wicaksono , Blasius Anggit; Rosidin , Undang (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
The Importance of Numeracy Literacy Skills in High School Students and the Effectiveness of the PBL Model Integrated with STEM-EDP. Numeracy literacy skills in students need to be improved, as these skills are essential in 21st-century education. This study aims to describe the effectiveness of implementing the PBL model integrated with STEM-EDP to enhance high school students' numeracy literacy skills on straight motion. The research was conducted at SMAN 13 Bandar Lampung using a quantitative experimental approach with a nonequivalent pretest-posttest control group design. The instrument used was an essay test. Learning with the PBL-STEM-EDP model has improved students' numeracy literacy skills. This is evident from the average N-gain score in the experimental class, which was 0.79, compared to 0.33 in the control class. These data indicate a significant difference in numeracy literacy skills between the experimental and control classes. This finding is supported by the results of the Independent Sample T-Test, Paired T-Test, and ANCOVA, which yielded a Sig. (2-tailed) value of 0.000 < 0.05. Thus, it can be concluded that the PBL model integrated with STEM-EDP is effective in improving students' numeracy literacy skills. Additionally, the effect size value of 0.802 indicates that the PBL-STEM-EDP model has a strong influence on enhancing students' numeracy literacy skills. Future researchers should not only observe students' initial and final abilities but also examine the learning process in more detail.